Pandemic Dreams: Network Analysis of Dream Content During the COVID-19 Lockdown - Pesonen, Anu-Katriina; Lipsanen, Jari; Halonen, Risto; Elovainio, Marko; Sandman, Nils; Mäkelä, Juha-Matti; Antila, Minea; Béchard, Deni; Ollila, Hanna M.; Kuula, Liisa (Frontiers in Psychology, 2020)
Abstract We used crowdsourcing (CS) to examine how COVID-19 lockdown affects the content of dreams and nightmares. The CS took place on the 6th week of the lockdown. Over the course of one week, 4275 respondents (mean age 43, SD=14 years) assessed their sleep and 811 reported their dream content. Overall, respondents slept substantially more (54.2%) but reported an average increase of awakenings (28.6%) and nightmares (26%) from the pre-pandemic situation. We transcribed the content of the dreams into word lists and performed unsupervised computational network and cluster analysis of word associations, which suggested 33 dream clusters including 20 bad dream clusters, of which 55% were pandemic specific (e.g. Disease Management, Disregard of Distancing, Elderly in Trouble). The dream association networks were more accentuated for those who reported an increase in perceived stress. This CS survey on dream-association networks and pandemic stress introduces novel, collectively shared COVID-19 bad dream contents.